2015
DOI: 10.1016/j.neurobiolaging.2015.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Aβ-related hyperactivation in frontoparietal control regions in cognitively normal elderly

Abstract: The accumulation of beta amyloid (Aβ) peptides, a pathological hallmark of Alzheimers disease, has been associated with functional alterations in cognitively normal elderly, most often in the context of episodic memory (EM) with a particular emphasis on the medial temporal lobes. The topography of Aβ deposition, however, highly overlaps with fronto-parietal control (FPC) regions implicated in cognitive control/working memory (WM). To examine Aβ-related functional alternations in the FPC regions during a WM tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 72 publications
2
24
0
Order By: Relevance
“…Several previous studies have also observed positive relationships between AD pathology and BOLD response during episodic memory tasks (Sperling et al, 2009; Mormino et al, 2012; Elman et al, 2014) and executive tasks (Gordon et al, 2015; Oh et al, 2015). Considering WMH-BOLD relationships in CN older adults, there have been reports of both positive (Lockhart et al, 2015) and negative correlations (Nordahl et al, 2006; Venkatraman et al, 2010).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Several previous studies have also observed positive relationships between AD pathology and BOLD response during episodic memory tasks (Sperling et al, 2009; Mormino et al, 2012; Elman et al, 2014) and executive tasks (Gordon et al, 2015; Oh et al, 2015). Considering WMH-BOLD relationships in CN older adults, there have been reports of both positive (Lockhart et al, 2015) and negative correlations (Nordahl et al, 2006; Venkatraman et al, 2010).…”
Section: Discussionmentioning
confidence: 66%
“…Separate studies conducted with CN older adults have reported functional brain alterations during the performance of executive tasks associated with WMHs (Nordahl et al, 2006; Venkatraman et al, 2010) and more recently with AD pathology (Gordon et al, 2015; Oh et al, 2015). However, few if any studies have explored the impact of both WMH and AD pathology on functional brain activations using a common task paradigm and participant group.…”
Section: Introductionmentioning
confidence: 99%
“…SUVrs are obtained by comparing tracer uptake in target regions to a reference area devoid of specific uptake. By comparing SUVrs in AD patients with SUVrs obtained in healthy volunteers, previous studies derived cut-off thresholds that could discriminate between amyloid positive and amyloid negative individuals ( Barthel et al, 2011 ; Chiotis et al, 2015 ; Fleisher, 2011 ; Nordberg et al, 2013 ; Oh et al, 2015 ; Ong et al, 2015 ; Vandenberghe et al, 2010 ). Semi-quantitative amyloid burden is generally estimated on average (composite) SUVr based on neocortical regions, usually including frontal, parietal, temporal and cingulate regions ( Clark et al, 2012 ; Fleisher, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…First, there was no age-matched prevalence of FBB positivity in the normal subjects in this study. Only few studies on FBB have reported evidence that a proportion of cognitively normal older subjects reveal Aβ deposits in the brain [37]. Most studies have determined Aβ positivity in persons without dementia using PIB PET [28].…”
Section: Discussionmentioning
confidence: 99%